Exosomes as secondary inductive signals involved in kidney organogenesis - Krause, Mirja (J Extracell Vesicles, 2018)
The subfraction of extracellular vesicles, called exosomes, transfers biological molecular information not only between cells but also between tissues and organs as nanolevel signals. Owing to their unique properties such that they contain several RNA species and proteins implicated in kidney development, exosomes are putative candidates to serve as developmental programming units in embryonic induction and tissue interactions. We used the mammalian metanephric kidney and its nephron-forming mesenchyme containing the nephron progenitor/stem cells as a model to investigate if secreted exosomes could serve as a novel type of inductive signal in a process defined as embryonic induction that controls organogenesis. As judged by several characteristic criteria, exosomes were enriched and purified from a cell line derived from embryonic kidney ureteric bud (UB) and from primary embryonic kidney UB cells, respectively. The cargo of the UB-derived exosomes was analysed by qPCR and proteomics. Several miRNA species that play a role in Wnt pathways and enrichment of proteins involved in pathways regulating the organization of the extracellular matrix as well as tissue homeostasis were identified. When labelled with fluorescent dyes, the uptake of the exosomes by metanephric mesenchyme (MM) cells and the transfer of their cargo to the cells can be observed. Closer inspection revealed that besides entering the cytoplasm, the exosomes were competent to also reach the nucleus. Furthermore, fluorescently labelled exosomal RNA enters into the cytoplasm of the MM cells. Exposure of the embryonic kidney-derived exosomes to the whole MM in an ex vivo organ culture setting did not lead to an induction of nephrogenesis but had an impact on the overall organization of the tissue. We conclude that the exosomes provide a novel signalling system with an apparent role in secondary embryonic induction regulating organogenesis.